Agentif Movement Verb in Javanese Language Study of Natural Semantic Metlanguage - Hidayani, Isma (L'Geneus : The Journal Language Generations of Intellectual Society, 2020)
This study describes the categorization and meaning of agentive motion verbs in Javanese. In this research, Natural Semantic Metlanguage (MSA) theory is used. The data used are sourced from oral data, written data, and intuition data that were collected using the listening method and proficient method. Furthermore, the collected data were analyzed using the split method and the equivalent method. Then the results of the analysis are presented using formal methods and informal methods. The results show that the agentive motion verbs are categorized based on components (1) „at that time, X moves to a place?, (2) „at that time, X moves from a place?, (3) „at that time, X moves in front of Y ?, (4)„ at that time, X moves above Y ?, (5)„ at that time, X moves inside Y ?, (6)„ at that time, X moves above Y ?, (7) „at that time, X moved sideways?. The meaning of the agentive movement verb is formed from the polysemi to MOVE / WANT, MOVE / THINK, and MOVE / FEEL.\